A review of all Recent species in the genus Novocrania (Craniata, Brachiopoda) - Robinson, Jeffrey H (Zootaxa, 2017)
The Recent species in the craniid genus Novocrania are reviewed, based on the examination of actual specimens wherever possible, especially for species named from one or a few specimens. The fourteen Recent species currently in the literature are reduced to eight; five species names are synonymized. One species name was given to a specimen that is not a craniid. The wide morphological ranges of the remaining Novocrania species are described and figured and the extended geographical ranges illustrated. Diagnoses of the remaining species are provided. The long-standing debate whether Novocrania anomala and N. turbinata are separate species or synonyms is resolved; they are separate species. New molecular analyses and a relative time-tree are provided by Cohen et al. (Appendix 1), the time-tree is calibrated herein and the results of Cohen et al. (2014; Appendix 1) and the time tree are discussed. The likelihood of craniid long-distance migration based on their geographical ranges is discussed.